2021
DOI: 10.1080/15538362.2021.1930626
|View full text |Cite
|
Sign up to set email alerts
|

Convective Hot-air Drying of Green Mango: Influence of Hot Water Blanching and Chemical Pretreatments on Drying Kinetics and Physicochemical Properties of Dried Product

Abstract: Currently, there is a growing market demand for dehydrated green mango powder for the development of value-added products. Preservation of green mangoes through drying is a good option. In this study, the influence of pretreatments and drying temperatures on drying kinetics and physicochemical properties of dried product was investigated. The sliced (4 mm thickness) green mango samples were pretreated with hot water blanching at 98°C for 3 min, 3% (w/v) ascorbic acid, and 3% (w/v) calcium chloride solutions fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
7
10
0
Order By: Relevance
“…The profile in Fig. 2 a–c conforms to other reported profiles on the drying of agricultural fruits, vegetables, and crops 35 . The profile showed that MBF drying occurred in three stages at all the tested pretreatment types and drying temperatures.…”
Section: Resultssupporting
confidence: 87%
“…The profile in Fig. 2 a–c conforms to other reported profiles on the drying of agricultural fruits, vegetables, and crops 35 . The profile showed that MBF drying occurred in three stages at all the tested pretreatment types and drying temperatures.…”
Section: Resultssupporting
confidence: 87%
“…The higher ascorbic acid content was observed in powders dried at 50 °C than those dried at 60 °C and 70 °C which might be due to oxidation and heat sensitive nature of ascorbic acid. Similar decline in ascorbic acid content was reported by Mishra et al (2021) [13] in green mango powder. The decrease in ascorbic acid during storage might be due to increase in the moisture content as well as atmospheric temperature, oxygen and presence of trace metals (Hymavathi and Khader, 2005) [6] .…”
Section: Ascorbic Acidsupporting
confidence: 89%
“…As the drying process progresses, the moisture content of samples decreases until reaching the desired final moisture or an operational limit of the product [76]. The literature identifies that increasing the drying temperature increases the moisture removal rate from samples and, therefore, reduces the drying time [49].…”
Section: • Operating Conditionsmentioning
confidence: 99%